ENHANCING STUDENT’S CHARACTER THROUGH INNOVATIVE CURRICULUM: A STUDY ON THE IMPLEMENTATION OF P5-PPRA IN MADRASAS - Zahrah, Fatimatuz; Amaliyah, Rahmatul (The Ministry of Religious Affairs, The Republic of Indonesia, 2024)
The decline in student character requires an optimal solution. Strengthening the character of students is carried out in various ways, one of which is the independent curriculum innovation and 5PPRA. Madrasas try to instill various good characters that can become provisions for life in the future. This research aims to analyze the implementation of P5PPRA, the effectiveness of implementing P5PPRA, and the obstacles and solutions in the process of strengthening character with P5PPRA. This research is a critical literature review reviewing 25 articles from 2019 to 2024 and focuses on research progress regarding the independent curriculum and P5PPRA. The formulation and findings of this research are that the implementation of P5PPRA is carried out with maximum preparation and implementation, instilling character according to needs, and integration of intracurricular, extracurricular, and co-curricular, and innovative design. The effectiveness of implementing P5PPRA has succeeded in instilling religious and social character, increasing creativity and learning outcomes. Barriers to implementing P5PPRA include a lack of teacher and madrasah readiness, inadequate facilities and infrastructure, and equitable distribution of education. The implications of this research show that innovation in strengthening character with P5PPRA must be accompanied by teacher and madrasah readiness and completeness of infrastructure. Full involvement in the three main points of character education, namely between family, school, and community, is recommended as a real effort to instill character values in the nation's future generations.